The US ABM system and global strategic stability - V. Mizin (Международная аналитика, 2016)
The problems of antimissile defense constitutes one of the key issues of global arms control domain of today. No advancement toward the lowering of global military threat, reciprocal reduction of nuclear weapons’ arsenals and the solving of contemporary tasks in the vast realm of today’s strategic stability are feasible, if a suitable arrangement on it is not to be found. At the same time, this conundrum is the major irritant in the Russia-West interrelationship, first and foremost, in our dealings with the NATO military-political alliance led by the USA. Therefore, finding the mutually acceptable solutions to this end would have promoted the consolidation of mutual trust and created the prerequisites for moving toward a safer and more stable world. The paper suggests a set of specific urgent steps that would show the ways out of the current negotiating impasse related to the ABM problematic and created the basis for a potential agreement while not afflicting the national security of any state in the world.